Evaluation of nanosilver solution stability using UV-Vis spectral absorbency analysis and antibacterial activities on Escherichia coli and Staphylococcus aureus - Thi Trang, Nguyen; Thi Thao, Do; Thi Nga, Nguyen; Thi Cuc, Nguyen (Vietnam Journal of Biotechnology, 2021)
Recently, the use of nanomaterials in industrial and technological applications for various fields is quickly growing. The “green” synthesis of metallic nanoparticles has received increasing attention due to the development of eco-friendly technologies. In our previous research, silver nanoparticles have been successfully prepared in gelatin (Ag/Gelatin sample), Gelatin/Chitosan (Ag/Gelatin/Chitosan sample) and chitosan (Ag/Chitosan sample) suspensions using a chemical reducing agent. For this purpose, biological grade gelatin and chitosan were used as reducing and stabilizing agents without special physical conditions. The most advantage of this work is using a renewable material like gelatin as a reducing factor, which is eco-friendly agent. However, one of the most important issues related to those nanofluids is their stability, and it remains as a big challenge to achieve desired applications in future. Thus, all obtained nanosilver samples were characterized by UV-Vis spectroscopy and evaluated the stability of antibacterial activity on Escherichia coli, Staphylococcus aureus. The absorption spectra results of the samples, which were measured after storage for three months, illustrated that the absorption peaks of the silver nanoparticles in Ag/Gelatin and Ag/Chitosan had shifted slightly from 423 to 425 nm and 435 to 440 nm, respectively. Whereas, the absorption peak for the Ag/Gelatin/Chitosan remained the same at 423 nm. In addition, after storage for three months, Ag/Gelatin/Chitosan sample showed antibacterial activity better than the two remaining samples with the reduction of inhibition zones is insignificant at 21.5 ± 0.25 mm while testing on Escherichia coli and at 15.5 ± 0.25 mm on Staphylococus aureus. The results suggested that silver nanoparticles were prepared in Gelatin/Chitosan composition showing promising stability and antibacterial activity which are beneficial for various/diversed/further applications.